Continuous assessment for improved higher education achievement in business management (2011)
"This study investigated the extent to which continuous assessments (CAs) improved higher education learning achievement in Business Management. Survey research design was used. Multistage sampling technique was employed, resulting in sample sizes of 10 lecturers and 200 students from two higher institutions of learning. A continuous assessment for improved learning scale was designed for data collection. The data from the study were analysed using descriptive and correlation statistics. Three research questions were tested and the results showed that test and individual assignment are most commonly used techniques for measuring students' academic performances while group assignments were rarely used. The result also indicated that the group assignments were rarely used. The result also indicated that the lecturers do not use the feedback to provide remediation and do not mark continuous assessment test while some do not have proper records for CA scores. Most of the lecturers agreed that the most frequently used continuous assessment techniques were tests and assignments. Furthermore, there was significant relationship between continuous assessments and students, achievement in Business Management. Consequent upon these, it is recommended that lecturers should make use of other continuous assessment techniques such as group assignment, peer assessment, projects, term paper, and classroom observation to measure students' academic achievement among others. They should, likewise, ensure that remediation is provided. Records of continuous assessment scores should be kept for immediate and delayed remediate. Finally, seminars and workshops should be organized to educate lecturers and stakeholders in the education industry on the essence of continuous assessments in improving achievement at the higher education level"